Competency-Based Theological Education and the Contemporary Seminary - Anderson, Kenton C. (Christian higher education, 2025)
As a promising direction for the future of theological education, Competency-Based Theological Education (CBTE) has been both enthusiastically and critically received. While still early in its development and recognition, several accreditors, churches, agencies, and their seminaries have begun to embrace CBTE in the hopes of a brighter future for the work of ministry leadership development. More a set of values than a particular model of education, CBTE represents a paradigm shift in the practice of Christian higher education. Its emphasis upon collaborative mission, contextual discipleship, and mentored teamwork offers the contemporary seminary the opportunity to align with the mission of the church as a way toward mutual flourishing.